The Effect of Intellectual Capital Disclosure, Company Size, and Capital Structure on Financial Sustainability with Company Performance as a Mediating Variable - M. Syukrihady Irsyad; Riza Reni Yenti (Journal Research of Social Science, Economics, and Management, 2025)
The rapidly growing technology sector in Indonesia faces significant challenges in maintaining financial sustainability amid dynamic market conditions and intense competition. This study addresses the problem of understanding how intellectual capital disclosure, company size, and capital structure influence financial sustainability, particularly examining the mediating role of company performance. The research aims to provide empirical evidence on these relationships using data from 13 technology companies listed on the Indonesia Stock Exchange during 2018–2023. Employing a quantitative approach, path analysis and the Sobel test were used to analyze 68 observations, assessing both direct and indirect effects. Results show that intellectual capital disclosure directly affects financial sustainability but does not significantly influence company performance as a mediator. Conversely, company size and capital structure have both direct and partial indirect effects on financial sustainability mediated by company performance. Fixed asset growth was used as a control variable but showed no significant effect. The findings support signaling and agency theories, emphasizing the importance of managing intellectual assets, firm scale, and capital policies to foster sustainability. These insights offer practical implications for managers and policymakers in Indonesia’s technology sector, highlighting strategies to enhance financial stability and growth in a competitive global environment. Future studies should explore qualitative variables such as leadership, organizational culture, and conduct longitudinal research to capture evolving dynamics.